DIABETIC KETOACIDOSIS: WHEN THE LACK OF INSULIN BECOMES AN EMERGENCY (CIPEEX, 2025)
Introduction: Diabetic ketoacidosis (DKA) is a metabolic emergency primarily associated with type 1 diabetes, but can also occur in type 2 diabetes with the use of SGLT2 inhibitors and insulin reduction. It involves hyperglycemia, lipolysis, ketosis, and metabolic acidosis. Treatment includes fluid replacement, insulin, and electrolyte correction. In mild cases, the subcutaneous route has been shown to be effective. Management should be individualized to reduce complications. Objective: To investigate the pathophysiology and emergency management of diabetic ketoacidosis due to insulin deficiency. Methodology: This is an integrative literature review based on five articles, searched in the PubMed and Scientific Electronic Library Online (SciELO) databases. The review was conducted in 2025 using the following Health Sciences Descriptors (DeCS): "Diabetic ketoacidosis," "Insulin," "Ketones," and "Metabolic acidosis." Articles published between 2020 and 2025 were included. Articles published prior to 2020, those not classified as free or meta-analyzed, or that did not answer the guiding question "What are the mechanisms and emergency procedures in diabetic ketoacidosis due to insulin deficiency?" were not analyzed. Results: Insulin deficiency is the main factor in diabetic ketoacidosis, stimulating lipolysis, ketogenesis, and metabolic acidosis. Intravenous insulin is the standard of care, but the subcutaneous route is safe in mild cases. SGLT2 inhibitors increase the risk, especially with insufficient insulin. High BMI, insulin resistance, and dehydration also contribute. Management requires strict monitoring and individualized approaches. Conclusion: Therefore, diabetic ketoacidosis is a serious complication of insulin deficiency, causing intense lipolysis, ketosis, and metabolic acidosis. Treatment should be immediate, with hydration, electrolyte correction, and insulin. The subcutaneous route is effective in mild, monitored cases. SGLT2 inhibitors require caution in at-risk patients. Therefore, management should be individualized based on the evidence.